Smooth Decompositions of Triebel-Lizorkin and Besov Spaces on Product Spaces of Homogeneous Type. (22nd July 2014) - Liao, Fanghui; Liu, Zongguang; Zhang, Xiaojin
Abstract : We introduce Triebel-Lizorkin and Besov spaces by Calderón's reproducing formula on product spaces of homogeneous type. We also obtain smooth atomic and molecular decompositions for these spaces.